STEREOTYPING OF THE IMAGE OF POLES IN UKRAINIAN LITERATURE IN THE EARLY TWENTIETH CENTURY WITH A FOCUS ON CONTEMPORARY REMINISCENCES - Kupidura, Ryszard (Porównania, 2014)
The first part of the article is a reflection on the state of research of the Polish-Ukrainian cultural dialogue. The author argues that the dialogue determined the asymmetrical nature of the subject of this studies, which in turn resulted in the marginalization of certain areas of research (e.g. images of Poles in the Ukrainian literature). In the following part he discusses in detail the Polish characters appearing in Ukrainian literature of the period of modernism (Mykhailo Kotsiubynsky, Volodymyr Vynnychenko) and postmodernism (Tanya Malarchuk, Irena Karpa). The juxtaposition of writers from two distant periods allowed to show the modifications to which images of Poles in Ukrainian literature have been subjected in the past hundred years, and also to prove that contemporary creations of Polish etnoimages continue to rely on stereotypes grounded in the collective imagination.